2016
DOI: 10.1002/jrs.4989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HPO42 and SCN on the hydrogen bond network of water: femtosecond OHD‐RIKES and FTIR measurements

Abstract: The influence of an ion on the hydrogen bond (HB) structure of water is of potential interest in various aspects. Herein, we studied the effects of HPO42− and SCN− on the HB network of water in their aqueous solutions by using both femtosecond optical heterodyne‐detected Raman‐induced Kerr effect spectroscopy (fs OHD‐RIKES) and Fourier transform infrared spectroscopy (FTIR) spectroscopy. We found that both the amplitude of the 180 cm−1 HB stretching band of water in the fs OHD‐RIKES fast Fourier‐transformed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The C-H stretching modes are from the carboxyl acid of the OA ligand. The broad peaks at 2,065~2,087 cm -1 found for the AgSCN-treated QDs are corresponding to the SCN functional group [32]. This broad peak is consistent with the C≡N bond of a thiocyanate bound to lead with a Pb−S bond.…”
Section: Resultssupporting
confidence: 61%
“…The C-H stretching modes are from the carboxyl acid of the OA ligand. The broad peaks at 2,065~2,087 cm -1 found for the AgSCN-treated QDs are corresponding to the SCN functional group [32]. This broad peak is consistent with the C≡N bond of a thiocyanate bound to lead with a Pb−S bond.…”
Section: Resultssupporting
confidence: 61%
“…The influence of an ion on the hydrogen bond (HB) structure of water is of potential interest in various areas. The authors studied the effects of HPO 4 2− and SCN − on the HB network of water in their aqueous solutions by using both fs OHD‐RIKES and FTIR spectroscopy …”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 50%
“…The authors studied the effects of HPO 4 2− and SCN − on the HB network of water in their aqueous solutions by using both fs OHD-RIKES and FTIR spectroscopy. [113] 12.4 | Time-resolved and ultrafast Raman spectroscopy Yanagisawa et al reported an improved stopped-flow time-resolved resonance Raman spectroscopy device for studying enzymatic reactions. The device was tested using myoglobin, where the formation reaction of a high-valent heme species and ferryl-oxo heme, was monitored by time-resolved resonance Raman spectroscopy after mixing a ferric myoglobin solution with a hydrogen peroxide solution.…”
Section: Other Coherent Nonlinear Techniquesmentioning
confidence: 99%